Swedishness at workplace . A case study of perceived cultural transfers in a Swedish multinational company and in its Portuguese subsidiary - Barroso,Margarida Martins (2018)
By analysing the case of IKEA, a Swedish multinational company, and its Portuguese subsidiary, this article debates how certain assumptions about national culture are used to justify work practices and how these are perceived by management. The research was based in the analysis of company documents and in 16 in-depth interviews with managers in the two countries. Results show a strong incorporation of national and organisational cultures in the company's image and in the narratives of management. Both the Portuguese and Swedish interviewees recognise a close association between the national (Swedish) and organisational culture in the company, though Portuguese managers tend to perceive the Swedishness of the organisation more strongly. The study case points out to particular processes of culture formation, transmission, dissemination and reception, influenced by material and symbolic circumstances of the countries involved.